2022
DOI: 10.1093/asj/sjac092
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Patient Experience: A Comprehensive Analysis of Plastic Surgery Online Reviews

Abstract: Background Subjective online physician evaluation is an important component of patient decision-making. Understanding reviews may improve satisfaction and build positive online reputation. Objectives Our objective was to analyze and compare the top predictive factors driving patient satisfaction across the most popular plastic surgery procedures. Methods Onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, staff interaction, bedside manner, health outcomes, complications, and postoperative care were also positive predictors of satisfaction. 35 Lack of bedside manner and postoperative care predicted a negative review. Online reviews can be based on either provider- or patient-initiated satisfaction surveys.…”
Section: Current State Of Affairsmentioning
confidence: 99%
“…However, staff interaction, bedside manner, health outcomes, complications, and postoperative care were also positive predictors of satisfaction. 35 Lack of bedside manner and postoperative care predicted a negative review. Online reviews can be based on either provider- or patient-initiated satisfaction surveys.…”
Section: Current State Of Affairsmentioning
confidence: 99%
“…Fake claims may originate from both sides-some plastic surgeons may pay for fake reviews to inflate their rating. 3,4 Yelp does have proprietary algorithms that aim to hide fake reviews and/or verify patient identity, but the effectiveness of those tools cannot be conclusively determined. 3,4 Second, this study clearly demonstrated the polarizing nature of online reviews, as 80.3% of ratings received five stars and 13.5% received one star.…”
mentioning
confidence: 99%
“…3,4 Yelp does have proprietary algorithms that aim to hide fake reviews and/or verify patient identity, but the effectiveness of those tools cannot be conclusively determined. 3,4 Second, this study clearly demonstrated the polarizing nature of online reviews, as 80.3% of ratings received five stars and 13.5% received one star. Only 6.2% of reviews fell between two and four stars.…”
mentioning
confidence: 99%
See 2 more Smart Citations